The Labatory of the Future - Catalogue of the 18th International Architecture Exhibition : Volume 2 - Participating Countries - Lokko, Lesley, ....-; Biennale Architettura (Venetië : Biennale Architettura 2023, 2023)
The 18th International Architecture Exhibition, in Venice from May 20th to November 26th, 2023, is entitled The Laboratory of the Future. Conceived as “a kind of workshop, a laboratory where architects and practitioners across an expanded field of creative disciplines draw out examples from their contemporary practices that chart a path for the audience — participants and visitors alike — to weave through, imagining for themselves what the future can hold” (Lesley Lokko). The Catalogue of the Biennale Architettura 2023 is divided into two volumes and follows the organisation of the Exhibition, accompanying visitors and architecture enthusiasts through the exhibition spaces of the Arsenale and the Giardini, and towards the other projects showing in various locations in the city of Venice and in Forte Marghera, in Mestre.
Volume II of the Catalogue presents the National Participations and the Collateral Events of the 18th International Architecture Exhibition. The volume includes a series of illustrated texts that delve deeper into the projects on exhibit in the Pavilions and the Collateral Events at the Giardini, at the Arsenale and in various locations across Venice .
Keywords: Architectuur; Kunst